Tunas Air: Variasi Kemunculan dan Pengaruhnya terhadap Pertumbuhan Tanaman Jati (Tectona grandis) - Eny Faridah; Sapto Indrioko; Tuharno Tuharno (Fakultas Kehutanan Universitas Gadjah Mada, 2009)
Epicormics Root: Emerge Variation and Its Effect on Teak (Tectona grandis) Seedling growth Epicormic shoot is an adventitious shoot appearing from the dormant buds. The formation of the shoots is influenced by environmental conditions such as drought, excessive crown opening (by thinning) or by shoot death, but genetic factor also plays a role. Epicormic shoot is assumed to negatively affects plant growth. The study aims to identin) family variation in tendency to form epicormic shoots and to examine the effect of epicormic shoots on seedling growth of teakThe study was conducted in 2006 on teak plantation in compartments 37b, 38c, and 38d, RPH Mangkang, BKPH Mangkang, KPH Kendal. Plant materials used were 6-month teak plantation named as prospective teak plantation (Jati Prospektip. The research was done in Randomized Completely Block Design using 28 seedlots/families (clone number 1 to 28), 3 treeplots, and 3 blocks as replication; and 2 silvicultural treatments i.e. with epicormic shoots and without epicormic shoots (shoots being cut).Results showed that seedlots with the highest tendency to form epicormic shoots were number 5, 18, and 25, while those with the lowest tendency were 6, 10 and 12. The existence of epicormic shoots negatively affected plant growth both on height and stem diameter. In two months, height and stem diameter growth of plants without epicormic shoots were 81.0 cm and 1.29 cm respectively, while those with epicormic shoots were only 69.1 cm and 1.13 cm respectively. Two families showing the highest growth performance were families 14 (with height and diameter growth of 95.6 cm and 1.50 cm) and 22 (94.2 cm and 1.47 cm).